Q: What is the answer of (w plus 7)(w plus 3)?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-63=7w

Written out f(w) = w^2 + 7w + 12 there is no particular answer since it depends on what w is equal to. normally this type of question is posited as "Solve for w with f(w) = 0?" or to change its form to (ax + b)(cx + d) if f(w) = w^2 + 7w + 12 and f(w) = 0 then 0 = w^2 + 7w + 12 simply look at the factors of 12 1 x 12 2 x 6 3 x 4 now consider (w + a)(w + b) = w^2 + aw + bw + ab = w^2 + (a+ b)w + ab since you know 3 x 4 = 12 , and 3 + 4 = 7 this give you 0 = (w + 3) (w + 4) or f(w) = (w + 3)(w + 4) solving for zero w = either -3 or -4 as (-3 + 3)(-3 + 4) = (0)(1) = 0 or (-4 + 3)(-4 + 4) = (-1)(0) = 0 so depending on what you are actually looking for the answer is w^2 + 7w +12 = (w + 3)(w + 4) or -3 and -4

"16-7w plus 14-6w" is an algebraic expression - not an equation nor an inequality. It cannot be solved. So there is no way to determine the value of w and therefore the value of w-1.

Ill assume you mean for an are of a rectangle. w will stand for width. So you know the equation for a rectangle is L*W, so if length is 7W, then the area is 7W*W=Area or 7W^2

3w + 4e + 7w - e3 = 10w - e

Related questions

whats w stand for? -7w + 3(w+2)= -14

-4

509w

56w2 + 17w - 3 = 56w2 + 24w - 7w - 3 = 8w(7w + 3) - 1(7w + 3) = (7w + 3)(8w - 1)

-36 + 2w = -8w + w -36 + 2w = -7w -36 = -7w - 2w -36 = -9w w = -36/-9 = 4

-63=7w

Let's see if I can answer this. 4X + 6Y + 3Y + 4W + 6X - 7W = (4 + 6)X + (6 + 3)Y + (4 - 7)W = 10X + 9Y - 3W

Written out f(w) = w^2 + 7w + 12 there is no particular answer since it depends on what w is equal to. normally this type of question is posited as "Solve for w with f(w) = 0?" or to change its form to (ax + b)(cx + d) if f(w) = w^2 + 7w + 12 and f(w) = 0 then 0 = w^2 + 7w + 12 simply look at the factors of 12 1 x 12 2 x 6 3 x 4 now consider (w + a)(w + b) = w^2 + aw + bw + ab = w^2 + (a+ b)w + ab since you know 3 x 4 = 12 , and 3 + 4 = 7 this give you 0 = (w + 3) (w + 4) or f(w) = (w + 3)(w + 4) solving for zero w = either -3 or -4 as (-3 + 3)(-3 + 4) = (0)(1) = 0 or (-4 + 3)(-4 + 4) = (-1)(0) = 0 so depending on what you are actually looking for the answer is w^2 + 7w +12 = (w + 3)(w + 4) or -3 and -4

"16-7w plus 14-6w" is an algebraic expression - not an equation nor an inequality. It cannot be solved. So there is no way to determine the value of w and therefore the value of w-1.

224

Ill assume you mean for an are of a rectangle. w will stand for width. So you know the equation for a rectangle is L*W, so if length is 7W, then the area is 7W*W=Area or 7W^2

3w + 4e + 7w - e3 = 10w - e